This I Believe - Bonham Carter, Violet (Tufts Archival Research Center, 2006)
Violet Bonham Carter describes her Prime Minister father's influence on her life; and states her belief in the "absolute value of truth," in the diverse means (religion, philosophy, poetry, nature) of arriving at that truth, and in the courage to think honestly.